2013
DOI: 10.1016/j.dcn.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex involvement in creative problem solving in middle adolescence and adulthood

Abstract: Creative cognition, defined as the generation of new yet appropriate ideas and solutions, serves important adaptive purposes. Here, we tested whether and how middle adolescence, characterized by transformations toward life independency and individuality, is a more profitable phase than adulthood for creative cognition. Behavioral and neural differences for creative problem solving in adolescents (15-17 years) and adults (25-30 years) were measured while performing a matchstick problem task (MPT) in the scanner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…Notably, a substantial part of these studies revealed positive relations between PFC activations and creative performance (e.g., Carlsson, Wendt, & Risberg, ; Chavez‐Eakle, Graf‐Guerrero, Garcia‐Reyna, Vaugier, & Cruz‐Fuentes, ; Gibson, Folley, & Park, ). We investigated the neurodevelopmental changes of verbal creative idea generation in adolescents and adults (Kleibeuker et al., ). Based on the behavioral study described earlier, we predicted that adults (25–30 years) would outperform adolescents (15–17 years) on creative idea generation, and indeed, adults generated significantly more alternative uses than adolescents.…”
Section: Neural Correlates Of Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a substantial part of these studies revealed positive relations between PFC activations and creative performance (e.g., Carlsson, Wendt, & Risberg, ; Chavez‐Eakle, Graf‐Guerrero, Garcia‐Reyna, Vaugier, & Cruz‐Fuentes, ; Gibson, Folley, & Park, ). We investigated the neurodevelopmental changes of verbal creative idea generation in adolescents and adults (Kleibeuker et al., ). Based on the behavioral study described earlier, we predicted that adults (25–30 years) would outperform adolescents (15–17 years) on creative idea generation, and indeed, adults generated significantly more alternative uses than adolescents.…”
Section: Neural Correlates Of Creativitymentioning
confidence: 99%
“…Important new questions triggered by these results are what (brain) mechanisms are underlying training success in adolescents and to what extent training effects are related to the reorganization of the PFC and associated regulatory systems during adolescence (Keating, ; Steinberg, ). To examine these issues, we asked participants aged 15–16 years to perform an adapted version of the AUT (similar to the task described in Kleibeuker et al., ); fMRI images were acquired before and after the training program (Kleibeuker et al., ). Again, the core brain regions for creative ideation (SMG, AG, MTG) were consistently activated in adolescents and recruitment remained relatively stable after training.…”
Section: Creative Ideation Training In Adolescencementioning
confidence: 99%
“…In recent work [27] [13], scientists found linkage between the pre-frontal lobe and the creative mind and problem solving tendency. We reproduced this discovery by incorporating the optimal ROI clustering into the visualization design.…”
Section: Discussionmentioning
confidence: 99%
“…The raters displayed a satisfactory intra-class correlation coefficient (ICC = .89). Each participant was then scored on the mean rating of the originality scores of all of the solutions as in (Fink et al 2012;Kleibeuker et al 2013). …”
Section: Discussionmentioning
confidence: 99%